Implementasi Pembelajaran Seni Tari pada Kurikulum Merdeka Belajar di SMA Negeri 2 Mesuji Makmur - Julta, Arbi; Wahyudi, Wahyudi (LPPPI Publishing, 2025)
This study uses descriptive methodology and is classified as qualitative research. The purpose of this study was to determine and characterize the methods used in Class X of SMA Negeri 2 Mesuji Makmur for dance learning. This learning tool can be used by the researcher alone or combined with other equipment such as pencils and mobile phones. This study conducted data collection techniques including observation, literature review, interviews, and documentation. Data analysis involved the following steps: collection, reduction, classification, and conclusion. The findings of the study indicate that dance learning in the independent curriculum of SMA Negeri 2 Mesuji Makmur was less successful because some elements of implementation conflicted with the RPP. The instructor has used teaching strategies that are on the subject matter. However, teachers do not use tools such as Infocus in their learning, such as audio-visual materials that can affect student learning outcomes, when using local dance movements to educate about functions, meanings, and symbols.